Contralateral Axillary Lymph Node Metastases at the Time of Primary Breast Cancer Diagnosis: Curative or Palliative Intent? - C. Zhou; M. C. Richir; M. W. H. Leenders; B. L. A. M. Langenhorst; H. P. Knol; W. H. Schreurs (Case Reports in Surgery)
Contralateral axillary lymph node metastases (CAMs) in breast cancer patients are uncommon. CAM can be found at the time of primary breast cancer diagnosis or following prior treatment of breast cancer as a recurrence. This distinction may have important implications for disease staging and treatment selection. We report the case of a premenopausal woman with synchronous CAM. Despite extensive multimodality treatment, a recurrence was found 27 months after primary surgery. We reviewed the literature on histopathological tumor characteristics associated with CAM, lymphatic drainage of the breast to other sites than the ipsilateral axilla, and outcome of cases with CAM. This case contradicts current conceptions that CAM only develops from tumors with poor histopathological features. Emerging evidence shows that altered lymphatics play a central role in development of synchronous CAM. It is precisely this etiology that supports the concept that synchronous CAM occurs by lymphatic spread and not by hematogenous spread. Although controversial, treatment of synchronous CAM (without evidence of distant metastases) should therefore be of curative intent.